2007
DOI: 10.1007/s00464-007-9707-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of incisional hernia: Outcomes of 100 consecutive cases comprising 25 wall defects larger than 15 cm

Abstract: Minimal access procedures can provide good results in the repair of incisional hernia, even when the diameter is larger than 15 cm. Obesity is not a contraindication to laparoscopic repair. Further studies are expected to confirm these promising results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…This study demonstrated that a short mean operation time (overall, 116 minutes in our experience) and the ensuing reduced requirements for anesthetic drugs prevent early postoperative respiratory complications. Our mean operation time is lower than in Ferrari et al’s 25 L-G/M VH patients (205 minutes 25 ) and Grande and al.’s 35 cases (159 minutes 26 ); both sets of patients underwent LVHRTS.…”
Section: Discussioncontrasting
confidence: 65%
“…This study demonstrated that a short mean operation time (overall, 116 minutes in our experience) and the ensuing reduced requirements for anesthetic drugs prevent early postoperative respiratory complications. Our mean operation time is lower than in Ferrari et al’s 25 L-G/M VH patients (205 minutes 25 ) and Grande and al.’s 35 cases (159 minutes 26 ); both sets of patients underwent LVHRTS.…”
Section: Discussioncontrasting
confidence: 65%
“…These complications may demand surgical revision, with the removal or correction of the implanted device [5–9]. Furthermore, for up to 70% of patients with recurrent hernia, the surgeon must take into account that the previous treatment was performed with a mesh, which currently is somewhere in the abdominal wall [10, 11] and could complicate further treatment or lead to elaborate explantation.…”
mentioning
confidence: 99%
“…Staging of the ventral hernia has been helpful in surgical decision and in post-operative comparison of results [13]. The open intraperitoneal technique is appropriate for complex incisional hernias occurring in obese patients, but is contraindicated when laparoscopic access has been obtained; minimal access was shown to be feasible in patients with a larger mesh of 15 cm [14][15][16]. A cellular dermal matrix has been also suggested in this cases to resist to infection as well as porcine [3,17].…”
Section: Discussionmentioning
confidence: 99%
“…A cellular dermal matrix has been also suggested in this cases to resist to infection as well as porcine [3,17]. Open component separation, which allows autologous tissue repair with approximation of a midline fascia in patients with complex hernias, creates large skin flaps that prevent the visualization of epigastric vessels; this problem notwithstanding recurrence rates is similar for open and laparoscopic techniques [14,15,17]. Although there is a trend towards laparoscopic surgery the laparoscopic repair does not resolve the matter of the ventral hernia's being a problem with the abdominal wall [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%